Decoupling energy use and economic growth: Counter evidence from structural effects and embodied energy in trade. (1st April 2018) - Moreau, Vincent; Vuille, François
Highlights: The effects of energy efficiency measures are largely offset by economic growth in Switzerland. Index decomposition analysis shows that structural effects are significant for in trade related activities. Energy intensity does not adequately reflect decoupling as embodied energy in trade is not accounted for. Indirect energy consumption in economic activities reached 81% of direct energy use. Abstract: Decoupling economic growth from energy consumption is a wide spread attempt to decarbonize economic activities and increase energy security. Almost all members of the European Union have decoupled the two since 2005 as measured by a steady decline in energy intensity, the ratio of final energy consumption and gross domestic product. Economic growth, energy efficiency and structural changes have all contributed to changes in energy intensity of economic activities at the national level. In this article, the authors analyze to what extent decoupling can be attributed to each of these three factors and in particular structural effects, namely deindustrialization and tertiarization, which shifts energy consumption abroad and re-imports it as embodied energy in products. We quantify the effects of structural changes, economic growth and energy efficiency measures as well as embodied energy in trade at the level of economic activities. The methodological approach combines decomposition and input-output analysis to address boundary cases where monetary trade surpluses meet energy trade deficits. Switzerland provides a case in point with the added hurdle of low data availability per economic activity over time. The results show that the share of embodied energy in imports has reached 81% of final energy consumption in economic activities. A comparison of energy intensities with and without embodied energy in trade shows that decoupling is more virtual than actual. Shifting energy intensive activities abroad improves domestic performance but worsens both overall energy use and security by relying on more indirect energy consumption. Energy indicators should therefore be adjusted to avoid potentially conflicting policy objectives between energy intensity and security as well as trade.